Pelatihan Pintar Mendidik Anak di Tengah Program Belajar Mandiri Siswa dari Pemerintah Karena Pandemi di Sukajaya Muara Tiga Pidie Aceh - Riyan Maulana; Muliadi Muliadi; Lidiana Lidiana (Janaka, Jurnal Pengabdian Masyarakat, 2022)
The material provided in this community service activity is related to how to educate children at home based on syariah and self-study programs from the government. This program took place in the Laweung Village and provided the people there with knowledge related to how to performance an independent learning program under parents control and educate children with a culture without suspecting children's behavior when learning with their gadgets as a courageous learning tool. This service activity is carried out using a training method, the participants who take part are gathered in a gampong hall so that it is hoped that the knowledge that can be conveyed is useful and useful for the Laweung gampong community to live in a healthy life and their sons and daughters can still study in peace.